The Role of Leadership In Enhancing Human Experience In Performance Management - Nani Sudiarti; Hedi Saepudin, Tubagus (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This study aims to investigate the role of leadership in improving human experience in performance management. Leadership has been recognized as a key factor in shaping an organizational culture that supports growth, innovation, and high performance. Human experience, as an important dimension of performance management, plays a crucial role in motivating, encouraging creativity, and strengthening employee engagement. This literature review investigates a variety of leadership theories and performance management approaches that focus on human experience. Among the key findings is the importance of transformational leadership, servant leadership, and transactional leadership in creating work environments that enrich the human experience. In addition, the integration of information technology in performance management has also opened up new opportunities to improve employee interaction and experience. The practical and theoretical implications of this research will be discussed further, along with suggestions for future research.